Peningkatan Hasil Belajar Peserta Didik menggunakan Model Kooperatif Tipe Team Quiz berbantuan Media PowerPoint Interaktif pada Pembelajaran IPS Kelas V SDN 10 Sumpur Kudus Selatan - Mawaddah Putri Yelsi; Siti Aisyah; Sry Apfani (ARZUSIN, 2025)
Social Studies (IPS) instruction in elementary schools often faces challenges such as low student participation, limited teaching methods, and minimal use of interactive learning media, all of which contribute to weak conceptual understanding and learning outcomes. This study aims to improve the quality of lesson planning, implementation, and student learning outcomes through the application of the Cooperative Learning Model of the Team Quiz type supported by interactive PowerPoint media, targeting fifth-grade students at SDN 10 Sumpur Kudus Selatan. The research employed Classroom Action Research (CAR) over two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection techniques included observation, documentation, and learning outcome tests, analyzed using both quantitative and qualitative descriptive methods. The results showed improvements in all aspects of learning. The average planning score increased from 74.95% (good) in Cycle I to 85.71% (very good) in Cycle II. Teacher activity improved from 76.35% to 83.3%, and student activity rose from 69.7% to 83.3%, both categorized as very good. The average student learning outcomes increased from 76.1% to 84.53%. These findings indicate that the Cooperative Team Quiz model supported by interactive PowerPoint is effective in enhancing student engagement, instructional quality, and Social Studies learning outcomes. The practical implication of this study highlights the importance of adopting innovative, technology-based learning models to foster active, enjoyable, and meaningful classroom environments while promoting student engagement and independence.